DUAL TRAINING IN RUSSIA: FROM THE CONCEPT TO PRACTICE - Alexander A. Listvin (Russian State Vocational Pedagogical University, 2016)
The purpose of the present article is to judge and justify the conditions of system elements application of dual training at implementation of programs of professional education for increase of efficiency of functioning and quality of preparation of qualified personnel by institutions of the secondary professional education (SPE). Methods. The methods used in work involve the comparative analysis of practice of application of dual training in system of professional education of Germany and regions of Russia for the purpose of identification of the existing problems and definition of optimum organizational and legal and didactic conditions. Results. The essence of system of dual training, its strong and weaknesses reveals. Necessary and indispensable conditions of application of dual training in modern regional systems of professional education are proved. Scientific novelty. According to the author, modern publications on problems and ways of development of professional education in Russia contain enough antinomy of standard and legal and organizational and administrative character. In particular, operating by the concept «dual education», an identification of the practice-focused and dual training introduction «the list 50 of the most demanded in labor market, the new and perspective professions that demand secondary professional education» as opposed to the existing list of professions and the constitutional guarantee of public and free secondary professional education. Standard and legal, and didactic conditions of application of elements of dual training in regional systems of professional education are proved theoretically. Practical significance. Implementation of the research outcomes can be useful to pedagogical staff of institutions of secondary professional education, representatives of employers and Chambers of Commerce and Industry to the organization and use of system of dual training in training of skilled workers (serving) and experts of middle ranking.